Factors affecting mental health service delivery from primary healthcare facilities of western hilly district of Nepal: a qualitative study - Madhusudan Subedi; Gaurav Devkota; Puspa Basnet; Bijay Thapa (BMJ Open)
Aim To explore factors at different socioecological levels that affect mental health service delivery from primary healthcare (PHC) facilities of Arghakhanchi district, a western hilly district of Nepal.Background Mental health service delivery has seen four transformational shifts from Alma Ata to Astana Declaration. Mental Health Gap Action Programme has facilitated the delivery of evidence-based interventions on mental, neurological and substance use disorders by non-specialised health workers in PHC settings as well as advocated scaling up of mental healthcare through integration of mental health in PHC.Methods A cross-sectional qualitative study was conducted in Arghakhanchi district of Nepal from July to August 2019 that collected information through face-to-face key informant interviews of 16 purposively selected participants using validated interview guidelines. Thematic analysis was performed using RQDA package for EZR software. Validation of translated transcripts, member checking and inter-coder percent agreement were performed to maintain rigour in the study.Results Lack of mental health training and no authority to prescribe psychotropic medications coupled with lack of mental health commodities acted as barriers for mental health service delivery. Awareness regarding mental health and modalities of treatment to the community and provision of training and authority to prescribe psychotropic medicines were recommended by the participants for proper mental health service delivery.Conclusions Awareness regarding mental illness treatment modalities to the community and mental health training for healthcare service providers would help increase mental health service delivery from PHC facilities. Moreover, strengthened referral system and availability of psychotropic medicines at the PHC level would assist in mental health service delivery from PHC facilities. However, regular monitoring and supervision of the services being delivered is essential.